Cu2+-doped BiOIO3 prepared by hydrothermal fabrication nanosheets for photocatalytic oxidation of gaseous mercury under visible light. (1st March 2022) - Tang, Tianhang; Zou, Jianshu; Luo, Fei; Liu, Zhiyong; Wu, Sikai; Wang, Fangjun; Wang, Daolei; Wu, Jiang; Qi, Yongfeng; Li, Jiachen; Tian, Fengguo
Highlights: The crystallinity of the catalyst was affected by the different doping ratios of Cu ions, because doping with copper ions increases the lattice spacing of BiOIO3 . The photocatalytic reaction mechanism of Cu 2+ -doped BiOIO3 was proposed, and the photocatalytic removal of gaseous mercury was used to study the effect of copper ion doping BiOIO3 on the photocatalytic activity of the sample. Abstract: The Cu 2+ -doped BiOIO3 photocatalyst was prepared by hydrothermal method, with larger specific surface area and enhanced photocatalytic oxidation efficiency of elemental mercury. The crystallinity of the catalyst was affected by the doping ratios of Cu 2+ . The doping of Cu 2+ could make BiOIO3 easier to achieve electron-hole separation and migration and expands the light response range of BiOIO3 . The photocatalytic removal of gaseous mercury was used to study the effect of copper ion doping BiOIO3 on the photocatalytic activity of the sample, and the photocatalytic reaction mechanism of Cu 2+ -doped BiOIO3 was proposed.